Determination of Available Phosphorus in Compounded Cattle Feed using Citrate Buffer by ICP-OES - Shashi Kant Gupta; B. Pal; M. Jitiya; R. Chawla; R. Nair (Indian Journal of Animal Nutrition, 2023)
Phosphorus is a crucial macro-mineral for maintenance, growth, production and reproduction in animals. Generally, phosphorus content in feed and feed ingredients in not adequate to support the body functions optimally. Therefore, mineral mixture is added to feed and feed ingredients as a supplement to provide adequate minerals in addition to phosphorus. Phosphorus is absorbed, only if present in soluble form. There are some previously established methods of determination of the available phosphorus, but these are lengthy, complex and difficult to follow. Therefore, it was required to develop a simple method of determination of available phosphorus by using citrate buffer of pH 3 to extract available phosphorus. Then available phosphorus was analyzed using ICP-OES after microwave digestion of the extract.